(ху-2х+5у)*3+2(2ху+3х-6у) если х=1.2\7;у=- 5\6

(ху-2х+5у)*3+2(2ху+3х-6у) если х=1.2\7;у=- 5\6
Гость
Ответ(ы) на вопрос:
Гость
(ху - 2х + 5у)*3 + 2*(2ху +3х - 6у) = 3ху - 6х + 15у + 4ху + 6х - 12у = 7ху + 3у = у*(7х + 3) если х = 1. 2/7; у = -5/6, то: [latex]- \frac{5}{6}(7*1 \frac{2}{7}+3) = - \frac{5}{6}(7* \frac{9}{7}+3)=- \frac{5}{6}(9+3) =-\frac{5}{6}*12=- \frac{60}{6}=-10 [/latex] х = [latex]1 \frac{2}{7}= \frac{1*7+2}{7}= \frac{9}{7} [/latex] Ответ: -10
Не нашли ответ?
Ответить на вопрос
Похожие вопросы